Exercise Core Body Temperature is Adequately Regulated Following Spinal Cord Injury: A Meta-Analysis - Yang Zhang; Stevo Popovic; Dusko Bjelica (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
Damage to the spinal cord results in malfunction of sympathetic pathways, which consequently influences thermoregulation during exercise. A consensus view is that athletes with spinal cord injury (SCI) are at a heightened thermal strain than the able-bodied athletes. However, a number of studies have reported similar increases in core body temperature in both populations. This study presented an up-to-date review of core body temperature response to exercise, from a meta-analytic point of view. Inclusion criteria were persons with SCI and control population (either healthy persons or wheelchair athletes without SCI) completed an exercise trial and their core body temperature responses were recorded under the same environmental conditions. Effect of SCI on thermoregulatory capabilities was quantified as raw mean core body temperature difference. Twelve studies examining 100 persons with SCI (Cervical (C2) to Lumbar (L5)) and 97 persons without SCI were meta-analyzed. The exercise interventions were submaximal exercise and the unweighted means ± standard deviations heat index and exercise duration were 31.5±11.9°C and 57±20 min, respectively. Regardless of injury, core body temperature was not different: raw mean difference, 0.048°C; 95% confidence interval, -0.12°C to 0.22°C. In conclusion, under SCI sport-specific exercise and environmental conditions, SCI does not produce outsized thermoregulatory impact, though the influence could be variable as a result of different lesion levels.